Early Detection and Intervention for the Stressed Resident - Katherine Berg; Lee Ann Riesenberg; Dale Berg; Joshua Davis; Robert Hargraves; Arielle Schaeffer; Kathleen Mealey; Daniel King; Brian Little (Association of American Medical Colleges, 2013)
Abstract Introduction Stress in residents has been shown to adversely affect health care provision and patient safety. Stress also has a direct effect on the health and well-being of residents, resulting in an increased risk of burnout, depression, and alcohol abuse. The Accreditation Council for Graduate Medical Education (ACGME) requirements direct residency programs to attend to physician well-being and the prevention of impairment by supplying support and training in recognizing the signs of fatigue and impairment. Methods In response to the ACGME requirements, we developed a 90-minute workshop with a PowerPoint presentation and trigger tapes to be used to educate faculty, residents, and medical students about the early detection and intervention of stress in medical training. Results Since developing the workshop in 2006, we have presented it over 15 times to diverse audiences (more than 400 participants) of faculty, residents, and medical students. Discussion The workshop can be easily exported and adapted for use in residency programs across various institutions and specialties. We have found that a mixed audience (faculty with residents) may inhibit active discussion by residents. It should be noted that one 90-minute workshop is just a starting point for learning to identify signs of stress, to understand how and when to intervene, and to develop successful strategies for stress reduction.